Results of the applicability of a population screening protocol for prostate cancer in Chapecó-SC (Research, Society and Development, 2021)
Campaigns that encourage screening for prostate cancer in Brazil are carried out annually and advocate the use of digital rectal examination associated with serum dosage of prostate-specific antigen. Objective: To evaluate the results and applicability of a prostate cancer screening protocol in Chapecó-SC. Methods: Clinical data from epidemiological profile questionnaires and PSA dosage tests of 249 men, over 45 years of age, residents of Chapecó-SC and affiliated to Unimed, were analyzed by consulting the Hospital's database and laboratory tests Unimed Chapecó. Results: The sample consisted of 249 men whose mean age was 51.2 years. The mean PSA value of the sample was 0.82 ng/dL and 3.2% of the patients had their result above 2.5 ng/dL. 14.05% have a history of a first-degree relative with prostate cancer. Discussion: Evidence suggests that screening for prostate cancer is not necessary. However, in the United States, the US Preventive Services Task Force recommended not performing screening and there was an increase in distant metastases of prostate cancer in individuals over 75 years of age. The most current recommendation indicates that it should be done individually in patients between 55 and 69 years old, for early-stage diagnosis and reduction of overdiagnosis and overtreatment. Conclusion: In view of the data presented, individualization in tracking is more important than indiscriminate population tracking.